Contribution to the knowledge of Rheotanytarsus pellucidus species group from China (Diptera, Chironomidae): three new and one newly recorded species - Liu, Wen-Bin; Yao, Yuan; Chang, Tong; Yan, Chun-Cai; Lin, Xiao-Long (Zootaxa, 2022)
Three new species, Rheotanytarsus ashei Yao & Liu sp. n., Rheotanytarsus pinderi Yao & Liu sp. n. and Rheotanytarsus vallenduuki Yao & Liu sp. n. are described and illustrated as adult males. Rheotanytarsus oss Cranston, 1997 is newly recorded and re-described from China. An updated key to males of Rheotanytarsus pellucidus species group is presented.